ANALISIS DETERMINAN KEMISKINAN DI PROVINSI SUMATERA UTARA - Bernadeth YP Simangunsong; Charitin Devi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The purpose of this research is to gain knowledge and information about the factors that influence poverty in North Sumatra Province. This research is a quantitative study with a total sample of 21 observation periods from 2002 to 2022. The data analysis method uses multiple linear regression analysis. This study shows that there is a negative and significant effect of the education budget on poverty with a probability value of 0.0004 <0.05. While unemployment and inflation have no significant effect on poverty in North Sumatra Province. With a coefficient of determination of 71.66% which gives an interpretation that the variation in the independent variables can explain the dependent variable strongly. The results of further research also provide the conclusion that simultaneously the variables of the education budget, unemployment and inflation have a significant effect on poverty in North Sumatra Province.